Immune Response to the Rhodococcus equi infection in high and low antibody-producing mice (selection IV-A) - Pedrini, Sílvia C. B. [UNESP]; Acorci, Michele J. [UNESP]; Pinto, João G. G. [UNESP]; Silveira, Liciana V. A. [UNESP]; Oliveira, Silvio L. [UNESP] (Wiley, 2005)
Rhodococcus equi is a Gram-positive, facultative intracellular bacterium which infects macrophages and causes rhodococcal pneumonia and enteritis in foals. Recently, this agent has been recognized as an opportunistic pathogen for immunocompromised humans. Several murine experimental models have been used to study R. equi infection. High (H IV-A) and Low (L IV-A) antibody (Ab)-producers mice were obtained by bi-directional genetic selections for their ability to produce antibodies against sheep and human erythrocytes (Selection IV-A). These lines maintain their phenotypes of high and low responders also for other antigens than those of selection (multispeciflc effect). A higher macrophage activity in L IV-A mice has been described for several intracellular infectious agents, which could be responsible for their intense macrophage antigens (Ag)-handling and low Ab production. Due to these differences, L IV-A mice were found to exhibit a better performance to trigger an effective immune response towards intracellular pathogens. The objective of this work was to characterize the immune response of Selection IV-A against R. equi. H IV-A and L IV-A mice were infected with 2.0 × 10 6 CFU of ATCC 33701 +R. equi by intravenous route. With regards to bacterial clearance and survival assays, L IV-A mice were more resistant than H IV-A mice to virulent R. equi. L IV-A mice presented a higher hydrogen peroxide (H 2O 2) and nitric oxide (NO) endogenous production by splenic macrophages than H IV-A mice. L IV-A expressed the most intense cellular response, available by the Delayed-Type Hypersensitivity (DTH) reaction, which activated macrophages and produced more H 2O 2 and NO. The three times higher specific antibodies titres in H IV-A indicated that Selection IV-A maintained the multispecific effect and the polygenic control of humoral and cellular responses also to R. equi.
Keywords: Biozzi mice; Immune response; Macrophage; Rhodococcus equi; antibody; antigen; hydrogen peroxide; nitric oxide; animal model; antibody production; bacterial infection; cell activity; cellular immunity; controlled study; enteritis; erythrocyte; female; genetics; humoral immunity; hypersensitivity reaction; immune deficiency; immune response; macrophage; mouse; nonhuman; phenotype; pneumonia; sheep; spleen cell; survival; titrimetry; virulence; Actinomycetales Infections; Animals; Antibodies, Bacterial; Colony Count, Microbial; Disease Models, Animal; Female; Hydrogen Peroxide; Hypersensitivity, Delayed; Liver; Lung; Macrophages; Mice; Nitric Oxide; Spleen; Survival Analysis; Animalia; Bacteria (microorganisms); Murinae; Ovis aries; Posibacteria